Über den integralen Grenzwertsatz für die Konvergenz gegen das stabile Grenzgesetz - Mitalauskas, A. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Миталаускас. Об интегральной предельной теореме для сходимости к устойчивому предельному законуA. Mitalauskas. Integralinė ribinė teorema konvergavimui į stabilų ribinį dėsnį